Pes cavovarus in Charcot-Marie-Tooth compared to the idiopathic cavovarus foot: A preliminary weightbearing CT analysis. Issue 2 (February 2021) - Bernasconi, Alessio; Cooper, Lucy; Lyle, Shirley; Patel, Shelain; Cullen, Nicholas; Singh, Dishan; Welck, Matthew
Highlights: Charcot-Marie-Tooth cavovarus exhibits increased supination compared to idiopathic forms. It also presents with greater hindfoot varus malalignment compared to idiopathic forms. Weightbearing 3D imaging may enable to detect subtle differences between different types of cavovarus. Abstract: Background: Pes cavovarus is a foot deformity that can be idiopathic (I-PC) or acquired secondary to other pathology. Charcot-Marie-Tooth disease (CMT) is the most common adult cause for acquired pes cavovarus deformity (CMT-PC). The foot morphology of these distinct patient groups has not been previously investigated. The aim of this study was to assess if morphological differences exist between CMT-PC, I-PC and normal feet (controls) using weightbearing computed tomography (WBCT). Methods: A retrospective analysis of WBCT scans performed between May 2013 and June 2017 was undertaken. WBCT scans from 17 CMT-PC, 17 I-PC and 17 healthy normally-aligned control feet (age-, side-, sex- and body mass index-matched) identified from a prospectively collected database, were analysed. Eight 2-dimensional (2D) and three 3-dimensional (3D) measurements were undertaken for each foot and mean values in the three groups were compared using one-way ANOVA with the Bonferroni correction. Results: Significant differences were observed between CMT-PC or I-PC and controls ( p  < 0.05). Two-dimensional measurements were similar in CMT-PC and I-PC, except for forefoot arch angle ( p  = 0.04). 3D measurements (foot and ankle offset, calcaneal offset and hindfoot alignment angle) demonstrated that CMT-PC exhibited more severe hindfoot varus malalignment than I-PC ( p  = 0.03, 0.04 and 0.02 respectively). Conclusions: CMT-related cavovarus and idiopathic cavovarus feet are morphologically different from healthy feet, and CMT feet exhibit increased forefoot supination and hindfoot malalignment compared to idiopathic forms. The use of novel three-dimensional analysis may help highlight subtle structural differences in patients with similar foot morphology but aetiologically different pathology. Level of evidence: Level III, retrospective comparative study.